Acid pretreatment of sugarcane biomass to obtain hemicellulosic hydrolisate rich in fermentable sugar. (December 2020) - Morais, Wilson G.; Pacheco, Thályta F.; Corrêa, Priscila S.; Martins, António A.; Mata, Teresa M.; Caetano, Nídia S.
Abstract: The objective of this work was to find the ideal pretreatment conditions with high efficiency to obtain a hydrolyzate rich in fermentable sugars and low possible inhibitors levels. Thus, it was applied diluted phosphoric acid to pretreat the sugarcane biomass. Through a Central Composite Design, it was evaluated the influence of temperature, operating time and acid concentration. The pretreatment efficiency was verified by the concentration of total monosaccharides in the liquid fraction after the reaction. The phosphoric acid concentration of 4.95% at 80 °C, during 375 min, resulted in a hemicellulosic hydrolyzate with the highest concentration of fermentable sugars (saccharification greater than 99%), with the absence of HMF and furfural, and relatively low amounts of acetic acid.